Exploring adolescents’ experiences navigating the intersection of their gender, sport, and dietary identities: an interpretative phenomenological study - Deslippe, Alysha L.; Middleton, Georgia; Wu, Olivia Y.; Bergeron, Coralie; Cohen, Tamara R. (Frontiers in Nutrition, 2024)
Not all adolescents have positive sport experiences. Research has repeatedly identified ties between unfavorable eating patterns and food beliefs (i.e., a dietary identity) that hinder an athletes’ health and performance. Gender norms and pressures over idealized bodies (e.g., boys are muscular whereas girls are thin) play a critical role in the manifestation of unfavorable eating habits. However, most research has focused on the experiences of athlete girls in elite sport spaces (e.g., high performance), leaving gaps in our understanding of how diverse youth in high school spaces are impacted. To address this gap, we aimed to explore the intersections between adolescents’ sport, dietary and gender identities in high school. We conducted 33 interviews with high school athletes (n = 9 girls and n = 9 boys) and non-athletes (n = 4 non-binary, n = 6 boys and n = 5 girls) using methods informed by an interpretative phenomenological approach. We generated three themes capturing adolescents’ experiences: (1) De-gendering protein and muscles; (2) Food displays what I value; and (3) Being [too] masculine is bad. Athletes recognized ties between masculinity and sport, but spoke about traditionally masculine eating habits (e.g., valuing protein) and body ideals (e.g., being muscular) as part of their athletic identity, not gender. Regardless of sport involvement, adolescents altered their outward expression of their dietary habits to demonstrate pieces of their identities, like being an athlete (e.g., eating protein) or feminine (e.g., smaller bites). Adolescents also spoke about using food to pursue idealized bodies that show deviation from traditional gender norms. Finally, adolescents held conflicting views about masculinity as being both toxic and useful for competition. By understanding identity intersections, coaches, trainers, parents, and sport decisions-makers can make more informed decisions about sport policy, programs, and practice that involve dietary advice to support this population.